Taxonomy and some ecological aspects of meiobenthic harpacticoid copepods in coastal water of Peninsular Malaysia - Kassim, Zaleha (2000)
A study on the taxonomy and some ecological aspects of meiobenthic harpacticoid copepods found in coastal water of Peninsular Malaysia was conducted from June 1996 to August 1999. The taxonomic study was carried out using specimens collected from Langkawi Island, Pangkor Island, Port Dickson, Tanjung Balau, Tanjung Piai and Redang Island. A total of 40 species, representing 29 genera from 16 families of harpacticoid copepods were identified. All the 40 species were unrecorded species in Malaysian coast. For all species, description, illustration and taxonomic notes were give The study on some ecological aspects of meiobenthic harpacticoid copepods was carried out along Port Dickson coast. Samples were obtained from the established transects perpendicular to the sea using a transparent hand corer with the inner diameter of3.57 cm. Harpacticoid copepods were the second dominant group of meiobenthos found in the studied areas. They contributed between 15% to 60% to total meiobenthos found in the sediment. The density and diversity distribution of meiobenthic harpacticoid copepods along the shore was correlated significantly (p<0.05) with certain environmental factors, namely salinity, dissolved oxygen, percentage of silt, clay and sand, water content, ground water level, depth of brown layer and sorting type of sediment. The vertical and horizontal zonation was correlated with the concentration of chlorophyll a in the sediment. The horizontal zonation was also correlated with the percentage of clay. The different set of environmental factors that found to correlate with the meiobenthic harpacticoid copepod distribution in the different studied areas indicated that different beaches might have their own environmental factors that governed the distribution.